Rare Case of Late-Onset Narcolepsy Type 1 - Kovalská, Petra; Dostálová, Simona; Machová, Hana; Nytrová, Petra; Maurovich Horvat, Eszter; Šonka, Karel (Case reports in neurology, 2020)
A 69-year-old male developed symptoms typical of the diagnosis of narcolepsy type 1 without any previous triggering events. First, daytime sleepiness occurred, soon followed by cataplexy. Nocturnal polysomnography revealed rapid eye movement (REM) sleep behavior disorder, a apnea-hypopnea index of 25.8 events/h, and no sleep-onset REM. Multiple Sleep Latency Test showed a mean sleep latency of 2.1 min and REM sleep in 3 tests. HLA DQB1*06:02 was positive and hypocretin-1 in cerebrospinal fluid unmeasurable. A treatment with 50 mg clomipramine controlled the cataplexy; excessive daytime sleepiness was sufficiently managed by repeated naps. The administration of 0.25 mg of clonazepam subjectively improved REM sleep behavior disorder. Bilevel Positive Airway Pressure improved the apnea-hypopnea index without important influence on sleepiness. Our unique case demonstrates that even elderly subjects can develop narcolepsy type 1.
Keywords: Narcolepsy with cataplexy; Rare case; Elderly